Requisite of Feminal Adherence: Shadow of Shattered Relationships in Toni Morrison’s Sula - V. , Abigail; M., Rakesh Babu (International Journal of Psychosocial Rehabilitation, 2020)
This study analyzes the niceties and complexities of female bonding as exposed in Toni Morrison’s Sula and also inspects the effect of gender, race, and class on female relationships. The novel conveys how women face the difficulties flung by man-centric foundations and how it cases the themes of motherhood, friendship, and love. The study demonstrates the deep bonding that unfolds between Sula and Nel, which was further tested by communal ethics. Nel was the most obedient character who did submit herself to the conventional nature and rule of society. Sula, on the other hand, was an unconventional character who was only concerned about herself, and she was careless about society’s-imposed law on women. These two contrastive ideologies made them part from each other. The novel Sula is really fascinating as it presents many strong female characters. Morrison always encourages women to form bonds with each other. The successful girlhood bonds help the women to build new identities, comfort, and support each other during difficult times. The study conveys the message that female bonding can help in the survival of the Black community. It also proposes the need for female bonding as a way of fighting oppression. It focuses on the intensity of man-controlled society, which establishes a risk to female bonding and more often causes women’s estrangement. The findings of this study emphasize and examine the recuperating powers of women bonding, which enables women to conquer obstacles and to broaden female kinship into female solidarity.